Jersey boys : music from the motion picture and Broadway musical : plus original recordings by Frankie Valli & the Four Seasons. (Hal Leonard, 2014)
Classic recordings from Frankie Valli and the Four Seasons combine with music recorded by the Broadway cast for the big screen adaptation of the Tony Award winning musical. Included are all of the group's number one hits, like Sherry.